2004
DOI: 10.1152/ajpheart.00122.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by glucose-insulin-potassium: dependence on KATPchannel opening and blood glucose concentration before ischemia

Abstract: We tested the hypothesis that glucose-insulin-potassium (GIK)-induced protection against myocardial infarction depends on ATP-dependent K(+) (K(ATP)) channel activation and is abolished by hyperglycemia before the ischemia. Dogs were subjected to a 60-min coronary artery occlusion and 3-h reperfusion in the absence or presence of GIK (25% dextrose; 50 IU insulin/l; 80 mM/l KCl infused at 1.5 ml x kg(-1) x h(-1)) beginning 75 min before coronary artery occlusion or 5 min before reperfusion. The role of K(ATP) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…NDNH, non-diabetics/ non-hyperglycemic; NDH, non-diabetics/hyperglycemic. to fatal arrhythmias [17], impaired microvascular function with no-reflow phenomenon [18] and the decrease activity of K-ATP channels [19]. Hyperglycemia has a pathogenic role in thrombosis, thrombophilia and platelet aggregation [20] There is a large body of evidence suggesting association between myocardial infarction and inflammation.…”
Section: Pathophysiological Impact Of Hyperglycemia During Acute Myocmentioning
confidence: 99%
“…NDNH, non-diabetics/ non-hyperglycemic; NDH, non-diabetics/hyperglycemic. to fatal arrhythmias [17], impaired microvascular function with no-reflow phenomenon [18] and the decrease activity of K-ATP channels [19]. Hyperglycemia has a pathogenic role in thrombosis, thrombophilia and platelet aggregation [20] There is a large body of evidence suggesting association between myocardial infarction and inflammation.…”
Section: Pathophysiological Impact Of Hyperglycemia During Acute Myocmentioning
confidence: 99%
“…Another plausible explanation would be that although hyperglycaemia is considered to abolish the beneficial effect of GIK, 34 there was a theory that increased osmolarity of the extracellular space caused by hyperglycaemia with GIK infusion could reduce cellular oedema during ischaemia. 24,35 Indeed, hyperglycaemia frequently developed in the GIK group even in a study reporting positive results.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed an improvement in ventricular contractility after ischemic episodes with morphine and fentanyl (28). Besides participating in the triggering of the cascade of ischemic preconditioning, opioids also seem to mediate the memory phase in some animal species and the opioid-induced cardioprotection appears to be modulated by the activation of cardiac receptors, independent of the action of these drugs on the central nervous system [40][41] . It has been proposed that opioid-induced cardioprotection is processed by the activation of ATP-dependent potassium channels, possibly in the mitochondrial membrane (29).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Regarding the 2 receptor agonists, clonidine seems to be less effective than high thoracic epidural anesthesia in reducing perioperative stress and troponin release in patients undergoing CABG (40). Additionally, experimental and small clinical trials showed encouraging results for the improvement of myocardial performance in patients undergoing cardiac surgery with the infusion of a solution containing glucose, insulin and potassium (GIK) (41). The mechanism by which GIK solution promotes cardioprotection seems to be related to the restoration of the activity of the ATP-dependent potassium channels by insulin, since glucose decreases the activity of this channel and insulin infusion can decrease apoptosis induced by ischemia and reperfusion (42).…”
Section: Myocardial Protectionmentioning
confidence: 99%